Bone substitute with osteoinductive biomaterials: current and future clinical applications - Hotz, Günter; Herr, Gerhard (International journal of oral and maxillofacial surgery, 1994)
In craniomaxillofacial surgery, possible indications for the use of osteoinductive biomaterials are interposition in intraosseous defects, contour augmentation, and reconstruction of segmental defects. The experimental results in the field of bone morphogenetic protein (BMP) research within the last few years have shown that it is possible to combine osteoinductive proteins with suitable carrier materials to obtain new composite osteoinductive biomaterials. These carrier materials function as slow-delivery systems for BMP. By combination of BMP with different carrier materials such as various types of calcium phosphate ceramics, collagen or inactive collagenous bone matrix, and other organic and inorganic carriers, the biomaterial can be adapted to clinical demands in a wide range. In several experimental animal studies, we investigated nine different calcium phosphate ceramics and inactive rat bone matrix for their use as BMP carrier. All materials tested seem to be suitable carriers for BMP The first clinical applications are discussed.
Elektronische Reproduktion der Druck-Ausgabe 18. März 2005
Gesehen am 27.11.2025